An intergenerational social contract for common resource usage: A reality-check for Harsanyi and Rawls - Stephan Wolf (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2010)
This paper investigates how one can derive fair allocation shares for renewable and non-renewable resources from a Rawlsian standpoint. Since there are competing interests over limited resources both within and between generations, it is argued that the respective trade-offs call for a more complete view of the conflict, taking both problems and their interrelation into account. The welfare economic solution of interand intra-generational sum of utilities maximization is rejected since it fails to prove that such optimum would be chosen by veiled stakeholders in a Rawlsian original position. The individual utility maximizing agent behind the veil is, deprived of knowledge in which generation she will be born and which income group she will part of inside a generation, confronted with a general trade-off: more resources to one generation may improve the lot also for low income individuals, but decrease utility for positions in other generations per se. While the risk neutral agent in Harsanyi's tradition is indifferent between solutions yielding all the same average utility from resource endowment, a realistic degree of risk aversion both concerning the intra- and intergenerational position shape the distributional choice necessarily towards more egalitarian solutions. A crucial factor determining one generation's share of the resource pie for a non-renewable resp. the utilization rate for a renewable resource is discounting. A discount rate of zero, as requested by Rawls, necessarily leads to strictly egalitarian intergenerational regimes independent of inter-generational risk aversion, while the distribution within a generation may be, depending on the intra-generational rate, rather unequal. The paper concludes with the observation that unequal intergenerational distributions among generations can only be justified given sufficient compensation for resource loss by building up a (public) capital stock.
Keywords: 330